Triple-Stage Black Box Testing Manual - Mohd Hamdan, Hasbullah (2011)
In sofware development life cycle process, software testing; phase is the most important process. However, in producing a good software, software testing should be conducted in proper way by using the right techniques. Normally, novice developers who are lacking in experiences in conducting software testing encountered problems. Among the issues that they encountered are lack of resources and guidelines. Therefore, the objective of this study is to develop a procedure manual called as Triple-Stage Black Box Testing Manual in helping novice developers how to conduct software testing. The manual was developed by adopting the ADDIE manual development model. Basically, this manual consists of 3 stages, which have to be executed stage by stage in synchronized with software development life cycle process. Pre-validation was conducted to test ease of read and ease of understand by potential develepoers. Only 60% of the participants agreed that the manual is easy to read and easy to understand. However, all of them agreed that the procedures for each technique are clearly explained. All of them also agreed that the manual is a good step in providing assistance to young developers to conduct software testing. However, the proposed manual only focuses on 3 black box testing strategies. Some modifications could be done to expand the testing strategies by adding more black box and white box testing strategies. Thus, users can be guided in conducting a white box testing strategies as well.